Researches in Adult Learning and Education: the European Dimension - Sava, Simona; Novotny, Petr (Studies on Adult Learning and Education, 2016)
The book represents several contributions that guide the readers in the comprehension of the paradigmatic shift from adult/lifelong education, to adult/lifelong learning. At the same time it presents the contexts where adults learn: the organized contexts, such as the institutions and services, and the informal contexts. The book is one of a series dedicated to adult learning and education developed under the auspices of ESRALE (European Studies and Research in Adult Learning and Education) an EU supported project. Its companion books are Maria Slowey (ed.) Comparative Adult Education and Learning. Authors and Texts and Vanna Boffo, Paolo Federighi, Ekkehard Nuissl, Empirical Research Methodology in Adult Learning and Education. Authors and Texts.